Deuterium tritium fusion experiment device radiation shielding analysis and optimization - Zhao Shengqiang; Wu Xinghua; Cao Qixiang; Qu Shen; Zhang Long; Zhao Fengchao; Yin Miao (Frontiers in Energy Research)
As deuterium-tritium (D-T) fusion experiments progress, radiation shielding is a fundamental requirement for ensuring personnel safety of fusion devices. This study utilizes neutron-photon coupling code to analyze the penetration of high-energy neutrons through various shielding materials in spatially constrained fusion experimental devices. The effectiveness of neutron shielding was evaluated through transmission factor measurements. Following the principle of “moderation before absorption,” different material combinations were optimized to enhance neutron attenuation. Simulation results indicate that a three-layer shielding configuration (i.e., comprising tungsten carbide (WC, 30 cm), boron-doped polyethylene (PEB, 10 cm), and boron carbide (B4C, 10 cm)) provides shielding effectiveness nearly an order of magnitude higher than a 50 cm boron-doped PEB monolith, while exceeding the performance of a 50 cm WC monolith by 50%. Furthermore, verification through a plant neutron transport model confirmed consistency with simplified shielding calculation model simulation trends, validating the selection of optimized shielding materials. These results offer valuable insights for designing effective radiation shielding in future fusion reactor applications.